2022
DOI: 10.1371/journal.pone.0274237
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of antithrombotic therapy for patients with atrial fibrillation: The prospective global GLORIA-AF registry program

Abstract: Objective To assess baseline characteristics and antithrombotic treatment (ATT) prescription patterns in patients enrolled in the third phase of the GLORIA-AF Registry Program, evaluate predictors of treatment prescription, and compare results with phase II. Methods GLORIA-AF is a large, global, prospective registry program, enrolling patients with newly diagnosed nonvalvular atrial fibrillation (AF) at risk of stroke. Patients receiving dabigatran were followed for two years in phase II, and all patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The shift in treatment distribution had been largely explained by the approximately 50.0% reduction for no antithrombotic treatments (down from 42.0 to 22.0%). However, the landscape of anticoagulation with OACs for stroke prevention in patients with AF in China remains suboptimal compared with the Asia (61.6%) [ 28 ] and global (82.2%) [ 29 ] GLORIA-AF Phase III populations. The Chinese subgroup in the GLORIA-AF Phase III population was noted to be younger than the overall global GLORIA-AF Phase III population (mean [SD] age 66.8 [11.1] and 70.5 [10.6], respectively) [ 29 ] and with a lower body mass index (BMI; mean [SD] 24.73 [3.4] and 28.6 [6.4], respectively) [ 29 ]; a lower age and BMI has been associated with a lower probability of OAC prescription, especially in Asia [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The shift in treatment distribution had been largely explained by the approximately 50.0% reduction for no antithrombotic treatments (down from 42.0 to 22.0%). However, the landscape of anticoagulation with OACs for stroke prevention in patients with AF in China remains suboptimal compared with the Asia (61.6%) [ 28 ] and global (82.2%) [ 29 ] GLORIA-AF Phase III populations. The Chinese subgroup in the GLORIA-AF Phase III population was noted to be younger than the overall global GLORIA-AF Phase III population (mean [SD] age 66.8 [11.1] and 70.5 [10.6], respectively) [ 29 ] and with a lower body mass index (BMI; mean [SD] 24.73 [3.4] and 28.6 [6.4], respectively) [ 29 ]; a lower age and BMI has been associated with a lower probability of OAC prescription, especially in Asia [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the landscape of anticoagulation with OACs for stroke prevention in patients with AF in China remains suboptimal compared with the Asia (61.6%) [ 28 ] and global (82.2%) [ 29 ] GLORIA-AF Phase III populations. The Chinese subgroup in the GLORIA-AF Phase III population was noted to be younger than the overall global GLORIA-AF Phase III population (mean [SD] age 66.8 [11.1] and 70.5 [10.6], respectively) [ 29 ] and with a lower body mass index (BMI; mean [SD] 24.73 [3.4] and 28.6 [6.4], respectively) [ 29 ]; a lower age and BMI has been associated with a lower probability of OAC prescription, especially in Asia [ 30 ]. Other international real-world registries such as GARFIELD-AF and EORP-AF have reported that over two-thirds of patients with AF were receiving OACs [ 31 , 32 ], and at least one-third to one-half of all patients with AF were receiving OACs in other registries across the East Asia region [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that at least 70% of patients with non-valvular atrial fibrillation, who are treated for the prevention of ischemic stroke, or those treated for venous thromboembolism and its recurrence, are currently on DOACs, and only the remaining 30% are treated with VKAs. 4 , 5 However, there are still clinical conditions in which DOACs are not adequate. For example, VKAs are still the drugs of choice in the prevention of thrombosis in patients with mechanical heart valves and for the prevention of thromboembolic events in patients with antiphospholipid syndrome.…”
Section: Direct Oral Anticoagulants (Doacs)mentioning
confidence: 99%